Impact of risk aversion, reactance proneness and risk appraisal on travel destination risk perception: - Prince, Melvin; Kim, Young Kyu (Journal of Vacation Marketing, 2021)
The aim of the study is to investigate the motivational effects of tourist traits and risk appraisal on tourist destination risk perception. Risk appraisal involves subjective estimates of vulnerability to a threat and the threat’s consequential severity. Fear levels influence both of these elements of risk appraisal. Individual differences in reactance proneness and risk aversion are introduced into the study model to more fully account for differences in travel destination risk perceptions. The study design involves US adults, who have used their passports for international travel in the past 5 years. Travel risk assessments were studied for four destination sites: London, Tokyo, Kuala Lumpur and Istanbul. A general structural model is developed to test hypotheses about antecedents and consequents of risk appraisal and destination risk perception. © The Author(s) 2021.
Keywords: dept.mkt; peer-reviewed